2000
DOI: 10.1159/000018426
|View full text |Cite
|
Sign up to set email alerts
|

Adamantiades-Behçet’s Disease: Serum IL-8 Is a More Reliable Marker for Disease Activity than C-Reactive Protein and Erythrocyte Sedimentation Rate

Abstract: Background: Interleukin 8 (IL-8) has recently been under focused investigation because of its possible participation in the evolution of Adamantiades-Behçet’s disease. Objective: The reliability of IL-8 as a serological marker for the activity of the disease was investigated in a prospective consecutive trial of 34 cases. Methods: The activity of the disease was clinically evaluated by the number of actively involved organ systems registered on the day of blood sampling and by the presence of oral aphthous ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 12 publications
3
58
2
2
Order By: Relevance
“…Several reports have examined the clinical roles of IL-8 in the disease activity, that is, the existence of ocular inflammation and the other systemic symptoms of BD [2,14,18,22,29,30]. However, the majority of free IL-8 as well as free MCP-1 in the plasma rapidly adhere to the surfaces of erythrocytes [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have examined the clinical roles of IL-8 in the disease activity, that is, the existence of ocular inflammation and the other systemic symptoms of BD [2,14,18,22,29,30]. However, the majority of free IL-8 as well as free MCP-1 in the plasma rapidly adhere to the surfaces of erythrocytes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations on BD have reported the increased serum IL-8 [2,14,22,29] and spontaneous production of IL-8 by peripheral mononuclear cells [18,30] in BD. One recent report even suggested that serum IL-8 can be a more reliable marker of the disease activity, according to the number of actively involved organs, than C-reactive protein (CRP) or erythrocyte sedimentation rates (ESR) in BD [14]. However, since IL-8 and MCP-1 bind to human erythrocytes [17,21], it is often difficult to measure precisely the amounts of these chemokines in the peripheral blood [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells were currently shown to also be a source for IL-8, and a correlation between serum levels of IL-8 and disease activity has been suggested [28]. In addition, IL-8 was shown to be a more reliable marker for the activity of BD than C-reactive protein and erythrocyte sedimentation rate [29]. The present study confirms our previous results of stronger IL-8 expression in patients with active BD than in patients in the inactive stage and indicates an important role of IL-8 in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ambrose et al demonstrated significantly higher production of CXCL10/IP10 in blood monocytes of BD patients stimulated with IFNγ compared to HC, rheumatoid arthritis, and systemic lupus erythematosus controls [170]. There is even more robust evidence for CXCL8/IL8, a potent neutrophil chemoattractant, being implicated in BD pathogenesis, with some of the authors proposing that it could be a marker for vascular involvement and a more reliable marker for disease activity than the C-reactive protein or erythrocyte sedimentation rate [171][172][173][174].…”
Section: Chemokinesmentioning
confidence: 99%